Pathfinder - Schmidt, Anna, 1943- (Schmidt, Anna, 1943- Cowboys & Harvey Girls., 2020)
Return to a time when the West was Wild... Captain Max Winslow was once a pathfinder for the Army, blazing trails and keeping his brothers-in-arms safe. Now he's the star of a Wild West show, reminding curious audiences of days long gone. The world around him may be changing, but that doesn't mean he has to accept it-not when there are frontiers yet to be explored. When Max first sets eyes on no-nonsense Harvey Girl Emma Elliot, he knows that anything between them would be impossible. She's a realist embracing what the future holds, while he's a dreamer, determined to preserve the West he once knew. And yet something about Emma's strength of will calls to him. It isn't long before Max must decide: is there room in his dream for love, or will his resolve to hang on to the past jeopardize their future? Cowboys & Harvey Girls Series: Trailblazer (book 1) Renegade (book 2) Pathfinder (book 3)